(untitled) (Mongolian Journal of Agricultural Sciences, 2014)
We consider the impact territories of a regional system of nature management, which are centers of environmental stress in the Selenga River basin. Their studies involve assessing the pollution of natural environments and aims to develop measures to minimize their impact on the environment that will promote a regional system of ecological optimization of nature (RSPP), in general. DOI: http://dx.doi.org/10.5564/mjas.v11i2.239 Mongolian Journal of Agricultural Sciences Vol.11(2) 2013 pp.155-158